In situ grown CdS on 2D Cd-based porphyrin MOFs enhances the significant separation and transfer of charge carriers with an appropriate heterojunction during photocatalytic hydrogen evolution. Issue 16 (1st July 2022) - He, Youzhou; Jiang, Guangmei; Zhang, Chenghua; Tu, Qingli; Jiang, Yuxiao; Gu, Li; Wang, Song; Tan, Juan; Jiang, Menghan; Liu, Xingyan
Abstract : This work provided a novel and reliable idea for preparing the integrated metal-sulfides/2D-MOFs via in situ grown strategy to realize the significant separation and transfer of charge carriers. Abstract : In theory, unmodified porphyrin metal–organic frameworks (MOFs) could be used as an available photocatalyst due to their excellent visible light response. Herein, a convenient method was adapted to fabricate a material integrating CdS and Cd-based porphyrin MOFs (CdS/NS-Cd) for enhancing the photocatalytic hydrogen evolution performance, in which the uniformly dispersed CdS was grown in situ on the metal clusters (Cd–O clusters) of thin 2D Cd-based porphyrin MOFs (NS-Cd) with thioacetamide as a sulfur source. Its improved photocatalytic hydrogen evolution rate (1.5 mmol g −1 h −1 ) and high quantum efficiency (8.3% of 420 nm) compared to those of the bulk NS-Cd were mainly ascribed to the matched energy band structure and shortened transmission distance between 2D NS-Cd and CdS. This work provides a novel and reliable idea for preparing integrated metal-sulfides/2D-MOFs via an in situ growth strategy to realize significant separation and transfer of charge carriers.